Preliminary Study on the Combination Effect of Clindamycin and Low Dose Trimethoprim-Sulfamethoxazole on Severe Pneumocystis Pneumonia After Renal Transplantation - Gu, Zhun-Yong; Liu, Wen-Jun; Huang, Dan-Lei; Liu, Yu-Jing; He, Hong-Yu; Yang, Cheng; Liu, Yi-Mei; Xu, Ming; Rong, Rui-Ming; Zhu, Du-Ming; Luo, Zhe; Ju, Min-Jie (Frontiers in Medicine, 2022)
Abstract Objective: Evaluate the effect of the combination of clindamycin with low-dose trimethoprim-sulfamethoxazole (TMP/SMX) regimen on sever pneumocystis pneumonia (PCP) after renal transplantation. Method: 20 severe PCP patients after renal transplantation were included in this historical-control, retrospective study. 10 patients were treated with the stand dose of TMP/SMX (T group), the other 10 patients were treated with the combination of clindamycin and low dose TMP/SMX (CT group). Results: Although there was no significant difference in the primary outcomes between the two groups, the CT protocol could improve the PaO2/FiO2 ratio more significantly and rapidly after the 6th ICU day (1.51 vs 0.38, P=0.014). CT protocol also ameliorated the pulmonary infiltration and the lactate dehydrogenase level more effectively. Moreover, the CT protocol reduced the incidence of pneumomediastinum (0 vs. 50%, P=0.008), the length of hospital staying (26.5 vs. 39.0 days, P=0.011) and ICU staying (12.5 vs. 22.5 days, P=0.008). On the other hand, more thrombocytopenia (9/10 vs. 3/10, P=0.020) was emerged in the T group than in the CT group. The total adverse reaction rate was much lower in the CT group then in the T group (8/80 vs. 27/80, P<0.001). Consequently, the dosage of TMP/SMX was reduced in 8 patients, while only 2 patients in the CT group received TMP/SMX decrement (P= 0.023). Conclusion: The current study proposed that clindamycin combined with low-dose TMP/SMX was more effective and safer the than single use of TMP/SMX for severe PCP patients after renal transplantation. (NCT 04328688)